2016
DOI: 10.1007/s10853-016-9948-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of ordered Cr2O3 nanorods and Cr2O3 nanoparticles on fluorination of 2-chloro-1,1,1-trifluoroethane

Abstract: Ordered Cr 2 O 3 nanorods (Cr 2 O 3 -R) and Cr 2 O 3 nanoparticles (Cr 2 O 3 -P) were prepared by a hard template method with SBA-15 and a deposition-precipitation method, respectively. These catalysts were tested for the fluorination of 2-chloro-1,1,1-trifluoroethane (HCFC-133a) to synthesize 1,1,1,2-tetrafluoroethane (HFC-134a). It was found that both catalysts were very selective, with a HFC-134a selectivity of 98 %. However, the Cr 2 O 3 -R catalyst had an area specific reaction rate of 0.012 lmol m -2 s -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The peak with binding energy of 577 eV is attributed to Cr 2 O 3 . For pure Cr catalyst, additional peak with binding energy of 575.8 eV is detected, which is believed to be Cr­(OH) 3 . Similar with our previous study, small amounts of fluorinated Cr species are observed following pretreatment of CHClF 2 at 300 °C for 2 h (F content of 6.2 at%, as listed in Table S3).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The peak with binding energy of 577 eV is attributed to Cr 2 O 3 . For pure Cr catalyst, additional peak with binding energy of 575.8 eV is detected, which is believed to be Cr­(OH) 3 . Similar with our previous study, small amounts of fluorinated Cr species are observed following pretreatment of CHClF 2 at 300 °C for 2 h (F content of 6.2 at%, as listed in Table S3).…”
Section: Resultssupporting
confidence: 84%
“…For Cr/Al composite catalysts, as exhibited in Figure a, Cr 2p 3/2 is deconvoluted into two peaks indicating that there are two Cr states in composite catalysts. The peak with binding energy around 579 eV is assigned to Cr (VI) species . The peak with binding energy of 577 eV is attributed to Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 presents the results of X-ray photoelectron spectroscopy (XPS) experiments for Cr 2 O 3 -SCS and Cr 2 O 3 -C. Very similar peaks are observed for both catalysts. According to the deconvolution of Cr 2p 3/2 peaks, there are three Cr species both for Cr 2 O 3 -SCS and Cr 2 O 3 -C. The peak with binding energy of 576.1 eV indicates the existence of Cr(OH) 3 [19,32] and the peak at binding energy of 577.3 eV is suggested to be the typical peak of Cr 2 O 3 [33,34]. The peak at 578.7 eV is attributed to the CrO 3 species [19,35].…”
Section: Resultsmentioning
confidence: 99%
“…According to the deconvolution of Cr 2p 3/2 peaks, there are three Cr species both for Cr 2 O 3 -SCS and Cr 2 O 3 -C. The peak with binding energy of 576.1 eV indicates the existence of Cr(OH) 3 [19,32] and the peak at binding energy of 577.3 eV is suggested to be the typical peak of Cr 2 O 3 [33,34]. The peak at 578.7 eV is attributed to the CrO 3 species [19,35]. Clearly, Cr(OH) 3 , Cr 2 O 3 , and CrO 3 co-exist on the surface of Cr 2 O 3 -SCS and Cr 2 O 3 -C. The emergence of CrO 3 is most probably attributed to oxidation of Cr 2 O 3 at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation